2018
DOI: 10.1007/s12094-018-1931-3
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative adjuvant and very early salvage radiotherapy after prostatectomy in high-risk prostate cancer patients can improve specific and overall survival

Abstract: In this study the ART + ESRT presented benefits versus SRT in DFS, CSS, OS and MFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“… 13 Some articles were incapable of demonstrating a difference in either radiotherapy when it came to MFS rates, showing that either method was effective. 14 , 15 Through our literature review, ART and ESRT/SRT results when looking at MFS were similar. These results were not statistically significant ( p = 0.428), and therefore provide strong evidence for the null hypothesis that there is no difference between ART and ESRT when observing MFS rates.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“… 13 Some articles were incapable of demonstrating a difference in either radiotherapy when it came to MFS rates, showing that either method was effective. 14 , 15 Through our literature review, ART and ESRT/SRT results when looking at MFS were similar. These results were not statistically significant ( p = 0.428), and therefore provide strong evidence for the null hypothesis that there is no difference between ART and ESRT when observing MFS rates.…”
Section: Discussionmentioning
confidence: 62%
“… 2 , 3 , 7 , 9 , 10 , 12 Despite the fact that ART was seen as the preferable treatment in many of the peer review articles, a great deal of studies supported either method by demonstrating that ART and ESRT/SRT shared no statistically significant differences relating to OS. 14 , 15 , 16 , 17 , 18 To further provide evidence for this point, this review discovered that even when comparing data with other studies, OS rates in ART and ESRT/SRT were almost equivalent. These results were also insufficient in concluding that one method is better than the other, since the evidence was not strong enough to suggest that an effect exists between ART and ESRT/SRT (p = 0.770).…”
Section: Discussionmentioning
confidence: 98%
“…More recently it has been reported that salvage radiotherapy and adjuvant radiotherapy offer similar outcomes for event-free survival, although the use of salvage radiotherapy is preferred since side-effects are lower compared with adjuvant radiotherapy [3,4]. Although we confirm the need to redefine the role of adjuvant radiotherapy after radical prostatectomy, we believe that adjuvant radiotherapy should be the first choice in men with prostate cancer and high-risk pathological factors after radical prostatectomy.…”
Section: Dear Editormentioning
confidence: 52%
“…We congratulate Casas et al [1] for their work on the role of postoperative adjuvant and early salvage radiotherapy after prostatectomy in high-risk prostate cancer. In this paper, the authors compared radical prostatectomy plus adjuvant radiotherapy and early salvage radiotherapy versus salvage radiotherapy.…”
Section: Dear Editormentioning
confidence: 97%
“…Patients with prostate cancer must know that prostatectomy can cure their prostate cancer, but they must also know that depending on possible pathological factors, they may need other treatments such as postoperative RT and/ or HT to achieve a cure. Patients must also be aware that while prostatectomy may alter sexual potency and urinary continence, postoperative RT may produce further toxicity in addition to these previous complications [6]. Each specialist must explain the possible benefits and secondary effects of the treatments.…”
mentioning
confidence: 99%